Sex differences in multisensory speech processing in both typically developing children and those on the autism spectrum - Ross, Lars A.; Del Bene, Victor A.; Molholm, Sophie; Frey, Hans-Peter; Foxe, John J. (Frontiers in Neuroscience, 2015)
Background: Previous work has revealed sizeable deficits in the abilities of children with an autism spectrum disorder (ASD) to integrate auditory and visual speech signals, with clear implications for social communication in this population. There is a strong male preponderance in ASD, with approximately four affected males for every female. The presence of sex differences in ASD symptoms suggests a sexual dimorphism in the ASD phenotype, and raises the question of whether this dimorphism extends to ASD traits in the neurotypical population. Here, we investigated possible sexual dimorphism in multisensory speech integration in both ASD and neurotypical individuals. Methods: We assessed whether males and females differed in their ability to benefit from visual speech when target words were presented under varying levels of signal-to-noise, in samples of neurotypical children and adults, and in children diagnosed with an ASD. Results: In typically developing (TD) children and children with ASD, females (n= 47 and n=15 respectively) were significantly superior in their ability to recognize words under audiovisual listening conditions compared to males (n= 55 and n=58 respectively). This sex difference was absent in our sample of neurotypical adults (n= 28 females; n= 28 males). Conclusions: We propose that the development of audiovisual integration is delayed in male relative to female children, a delay that is also observed in ASD. In neurotypicals, these sex differences disappear in early adulthood when females approach their performance maximum and males “catch up”. Our findings underline the importance of considering sex differences in the search for autism endophenotypes and strongly encourage increased efforts to study the underrepresented population of females within ASD.